Gaya Kepemimpinan Transformasional Kepala Madrasah MIS Muhammadiyah 14 Talang Ulu Dalam Menghadapi Tantangan dan Perubahan Pendidikan - Linda Ayu Syafitri; Jumira Warlizasusi; Emmi Kholila Harahap (Education Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the application of transformational leadership by the principal of MIS Muhammadiyah 14 Talang Ulu in responding to educational challenges and changes. The study is motivated by the limited empirical research assessing how transformational leadership can drive innovation, collaboration, and character development in elementary Islamic schools. A qualitative case study approach was used, with data collected through in-depth interviews, observations, and documentation. Findings indicate that the principal effectively internalizes transformational leadership values through inspiring vision communication, teacher and staff empowerment, and promotion of technology- and character-based learning innovations. Challenges, including limited facilities and internal resistance, were overcome via collaborative strategies and continuous coaching. The study highlights the need for ongoing leadership training and strengthening of an adaptive madrasah organizational culture to ensure transformational leadership significantly enhances educational quality, innovation, and institutional reputation.